2020
DOI: 10.1097/hco.0000000000000730
|View full text |Cite
|
Sign up to set email alerts
|

Management of ventricular arrhythmias in patients with LVAD

Abstract: Purpose of review Left ventricular assist devices (LVADs) have extended the life expectancy of patients with heart failure. The hemodynamic support afforded by LVADs in this population has also resulted in patients having prolonged ventricular arrhythmias. The purpose of this article is to review the mechanisms of ventricular arrhythmias in LVADs and the available management strategies. Recent findings Recent evidence suggests that prolonged ventricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Approximately 20% of patients with LVAD experience VAs, mostly ventricular fibrillation, after LVAD implantation (3). A history of preimplant VAs, atrial fibrillation, prior cardiac surgery, and nonischemic cardiomyopathy; heart failure duration prior to LVAD (>12 months); advanced age; scarring at the cannula insertion sites; pump suction rates; and electrolyte disturbances have been reported as the most common causes of arrhythmias that develop after LVAD implantation (2,4,5). It has been reported that VAs are more common in the early period of LVAD implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 20% of patients with LVAD experience VAs, mostly ventricular fibrillation, after LVAD implantation (3). A history of preimplant VAs, atrial fibrillation, prior cardiac surgery, and nonischemic cardiomyopathy; heart failure duration prior to LVAD (>12 months); advanced age; scarring at the cannula insertion sites; pump suction rates; and electrolyte disturbances have been reported as the most common causes of arrhythmias that develop after LVAD implantation (2,4,5). It has been reported that VAs are more common in the early period of LVAD implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular arrhythmias (VAs) are one of the most critical complications that develop in patients with LVAD. VAs are common in the first 30 days of LVAD implantation (1,2). Although it has been reported that arrhythmias are generally well tolerated by patients with LVAD, their effects on mortality are still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, a recent systematic review of 18 studies showed that catheter ablation was associated with a decrease in rates of ICD therapies (57 vs. 24%), but VD recurred in 44% at a mean follow-up of 264 days [22].…”
Section: Mechanisms and Management Of Ventricular Dysrhythmiasmentioning
confidence: 99%
“…Scar-Related Reentrant Arrhythmia Potential cardiomyopathy after LVAD implantation is frequently accompanied by visible scar formation, which may be the cause of reentrant arrhythmia [30]. A metaanalysis showed that scar-related reentrant arrhythmia is the main mechanism of VT after LVAD implantation [31].…”
Section: Mechanical Effectmentioning
confidence: 99%